An investigation into the strategic facilities management contingencies implemented by commercial (office) property owners in response to drought risks in Cape Town - Porter, David (Department of Construction Economics and Management, 2025)
Water supply is of growing concern in both South Africa and globally due to climate change. Environmental, Social and Governance (ESG) is being encouraged as a result of climate change and reflects society's demands for organisations to make change that is sustainable for future generations. Water Management is one of the key factors relating to ESG and it was brought to the forefront in South Africa during the 2018 Drought. Strategic Facilities Management (Strategic FM) is recognised as the crucial link to ensure that organisations strategic goals are achieved through the management of facilities. This research project focuses on three case studies within the commercial (office) property sector in Cape Town. A literature review was conducted and the respondents in each case study was interviewed to determine what strategic FM contingencies were implemented by property owners to mitigate the potential risk of drought. The study revealed that property owners were relatively well prepared for the 2018 drought. Although the large majority of contingencies implemented were reactionary, most of them appeared to form part of the future plans or were part of various strategic risk plans and ESG objectives. The barriers and drivers to the implementation of Water Management Features and Initiatives (WMFIs) were explored and although one of the main barriers to implementing WMFIs was cost, the study highlighted that some cost effective measures were very affective at reducing water consumption. The 2018 drought tested the drought resilience of Cape Town Property owners and fast tracked change which ultimately resulted in both commercial property owners and society to be more resilient against water supply problems.